2009
DOI: 10.1111/j.1742-7843.2009.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Scheduling and Withdrawal of Carisoprodol on Prevalence of Intoxications with the Drug

Abstract: The centrally acting muscle relaxant carisoprodol has previously been shown to cause psychomotor impairment and to have a narrow therapeutic range. In Norway, carisoprodol was therefore reclassified to the highest scheduling level During the same period, the sales figures for carisoprodol decreased dramatically, and we observed a relation between the numbers of DUI cases, forensic autopsies and contacts to the NPIC concerning carisoprodol and the sales figures for the drug. This study showed that the reschedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Re‐scheduling of carisoprodol (a muscle relaxant with a misuse potential) to Schedule IV reduced carisoprodol utilization in the United States and poisoning calls in California . Similar trends were seen with re‐scheduling and later withdrawal of carisoprodol in Norway . Codeine is still available OTC in many countries, and re‐scheduling should be considered to target misuse.…”
Section: Discussionmentioning
confidence: 78%
“…Re‐scheduling of carisoprodol (a muscle relaxant with a misuse potential) to Schedule IV reduced carisoprodol utilization in the United States and poisoning calls in California . Similar trends were seen with re‐scheduling and later withdrawal of carisoprodol in Norway . Codeine is still available OTC in many countries, and re‐scheduling should be considered to target misuse.…”
Section: Discussionmentioning
confidence: 78%
“…This is a situation unlike the one for carisoprodol, where the correlation between sales numbers and findings in drugged drivers was very high; this indicates that most drug use came from legal sources. This drug was removed from the Norwegian market due to its potential for misuse and toxic effects [18,19]. Moreover, an Australian study found that alprazolam findings in drug-related deaths were more related to prescribed alprazolam than clonazepam in our study [20].…”
Section: Discussionmentioning
confidence: 88%
“…In the year 2000, the Drug Abuse Warning Network (Substance Abuse and Mental Health Services Administration, 2001) ranked carisoprodol as the 20 th most abused drug, and its nonmedical use more than doubled between 2004 and 2008 (Substance Abuse and Mental Health Services Administration, 2011). The abuse potential of carisoprodol in humans has been outlined in several reviews over the past decade (Bailey and Briggs, 2002; Hoiseth et al, 2009; Reeves and Burke, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…For carisoprodol, there is substantial evidence of abuse in humans (Bailey and Briggs, 2002; Hoiseth et al, 2009; Reeves and Burke, 2010); as well as confirmation that it is self-administered in monkeys (France et al, 1999). The discriminative stimulus effects of carisoprodol are similar to known GABAergic drugs of abuse (Gonzalez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%